2012
DOI: 10.1089/mdr.2011.0150
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibilities and Resistance Genes of Canadian Isolates ofActinobacillus pleuropneumoniae

Abstract: Actinobacillus pleuropneumoniae is the causative agent of porcine pleuropneumonia, a severe and highly contagious respiratory disease responsible for economic losses in the swine industry worldwide. Although antimicrobial resistance in A. pleuropneumoniae has been recently reported in different countries, the current situation in Canada is unknown. The aim of the current study was to determine the antimicrobial susceptibilities of 43 strains of A. pleuropneumoniae isolated in Canada. In addition, antimicrobial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 45 publications
5
46
0
1
Order By: Relevance
“…Only treatment with tetracycline was not effective, as expected. The result of tetracycline treatment resembles the results obtained in field studies with pigs, as treatment with this drug shows low efficacy due to high incidence of tetracycline resistance in A. pleuropneumoniae (Archambault et al, 2012). Thus, this result reinforces the notion that this model can be used to study the efficacy of antibiotic treatments used in the field for the control of porcine pleuropneumonia.…”
Section: Discussionsupporting
confidence: 74%
“…Only treatment with tetracycline was not effective, as expected. The result of tetracycline treatment resembles the results obtained in field studies with pigs, as treatment with this drug shows low efficacy due to high incidence of tetracycline resistance in A. pleuropneumoniae (Archambault et al, 2012). Thus, this result reinforces the notion that this model can be used to study the efficacy of antibiotic treatments used in the field for the control of porcine pleuropneumonia.…”
Section: Discussionsupporting
confidence: 74%
“…Antibiotic therapy is used at the onset of symptoms to prevent mortality and the spread of the infection. Commonly used agents for infection control include tiamulin, chlortetracycline, ceftiofur, tilmicosin, florfenicol, enrofloaxacin and penicillin (Archambault et al, 2012). Despite an increase in the number of penicillin G resistant isolates reported in the last decade in Canada, the United States, and Europe (Archambault et al, 2012;Gutierrez-Martin et al, 2006;Salmon et al, 2003;Vanni et al, 2012), penicillin is recommended as the first-choice antibiotic by guideline of prudent use of antimicrobials in animals (Guardabassi et al, 2008;CVMA, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Despite an increase in the number of penicillin G resistant isolates reported in the last decade in Canada, the United States, and Europe (Archambault et al, 2012;Gutierrez-Martin et al, 2006;Salmon et al, 2003;Vanni et al, 2012), penicillin is recommended as the first-choice antibiotic by guideline of prudent use of antimicrobials in animals (Guardabassi et al, 2008;CVMA, 2008). It is well known that b-lactamases represent the main mechanism of bacterial resistance to penicillin G but a number of reports demonstrate that biofilms also contribute to b-lactam resistance (Archambault et al, 2012;Ciofu and Høiby, 2008;Hengzhuang et al, 2013;Olson et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…These are more frequently associated with chronic diseases due particularly to an increased resistance to both conventional biocides and the host immune system (20)(21)(22). In this context, we have shown that A. pleuropneumoniae biofilm cells are 100 to 30,000 times more tolerant to antimicrobials than their planktonic counterparts (23).…”
mentioning
confidence: 88%